THE ROLE OF ANTIOXIDANTS IN MODULATING DRUG-INDUCED OXIDATIVE STRESS: A NUTRITIONAL APPROACH (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Oxidative stress, resulting from an imbalance between reactive oxygen species (ROS) and antioxidant defenses, poses a significant concern in drug therapy, as many pharmaceuticals induce oxidative damage leading to adverse effects. This paper explores the role of antioxidants in mitigating drug-induced oxidative stress, focusing on nutritional strategies to manage this issue. Antioxidants, both endogenous and exogenous, are crucial in neutralizing ROS and protecting cells from oxidative damage. Key antioxidants include vitamins C and E, selenium, and polyphenols, which have demonstrated potential in reducing oxidative stress associated with various drugs. The interaction between antioxidants and pharmaceuticals is complex; while antioxidants can alleviate oxidative damage, they may also affect drug metabolism and efficacy. Nutritional approaches, including the consumption of antioxidant-rich foods and cautious use of supplements, are essential in managing oxidative stress. This review highlights the need for a balanced approach to antioxidant therapy, considering potential interactions and individual health conditions. Future research should further investigate these interactions to develop effective guidelines for integrating antioxidants into drug therapy, enhancing patient safety and therapeutic outcomes.